Implementasi Sistem Manajemen Produk Berbasis Web untuk Optimalisasi Penjualan Kerudung pada Toko Iwiim Hijab - Muhammad Miftahusy Syifa; Muhyiddin Zainul Arifin (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to implement a web-based product management system to optimize sales processes at Iwiim Hijab Store. The background of the research lies in the challenges faced by the store, such as manual inventory management and unintegrated marketing strategies, which often lead to data recording errors, delayed information, and decreased operational efficiency. The system development method used is the Waterfall model, which includes the stages of analysis, design, implementation, testing, and maintenance. The system provides features such as automated inventory management, real-time transaction monitoring, and in-depth sales data analysis. The results of the system implementation show improvements in operational efficiency, data accuracy, and the effectiveness of sales strategies. Therefore, this system successfully supports the competitiveness of Iwiim Hijab Store in the Muslim fashion industry in a sustainable manner.